Naltrexone-Induced Cardiac Function Improvement is Associated With an Attenuated Inflammatory Response and Lipid Perioxidation in Volume Overloaded Rats - Dehe, Lukas; Mousa, Shaaban A.; Shaqura, Mohammed; Shakibaei, Mehdi; Schäfer, Michael; Treskatsch, Sascha (Frontiers in Pharmacology, 2022)
In previous studies, upregulation of myocardial opioid receptors as well as the precursors of their endogenous ligands were detected in the failing heart due to chronic volume overload. Moreover, opioid receptor blockade by naltrexone improved left ventricular function. In parallel, inflammatory processes through cytokines have been confirmed to play an important role in the pathogenesis of different forms of heart failure. Thus, the present study examined the systemic and myocardial inflammatory response to chronic volume overload and its modulation by chronic naltrexone therapy. Chronic volume overload was induced in male Wistar rats by applying an infrarenal aortocaval fistula (ACF) for 28 days during which the selective opioid receptor antagonist naltrexone (n = 6) or vehicle (n = 6) were administered via a subcutaneously implanted Alzet minipump. The ultrastructural, morphometric and hemodynamic characterization of ACF animals were performed using an intraventricular conductance catheter in vivo and electron microscopy in vitro. Co-localization of mu-, delta- and kappa-opioid receptor subtypes (MOR, DOR, and KOR respectively) with the voltage gated L-type Ca2+ channel (Cav1.2), the ryanodine receptor (RyR), and mitochondria in cardiomyocytes as well as IL-6, IL-12, TNF-alpha, and Malondialdehyde (MDA) were determined using double immunofluorescence confocal microscopy, RT-PCR and ELISA, respectively. In rat left ventricular myocardium, three opioid receptor subtypes MOR, DOR, and KOR colocalized with Cav1.2, RyR and mitochondria suggesting a modulatory role of the excitation-contraction coupling. In rats with ACF-induced volume overload, signs of heart failure and myocardial ultrastructural damage, chronic naltrexone therapy improved cardiac function and reversed the systemic and myocardial inflammatory cytokine expression as well as lipid peroxidation. In conclusion, antagonism of the cardiodepressive effects of the myocardial opioid system does not only improve left ventricular function but also blunts the inflammatory response and lipid peroxidation.